On pointwise statistical convergence of order ? of sequences of fuzzy mappings - Et, Mikail; Tripathy, Binod Chandra; Dutta, Amar Joyti (Academic Publication Council, 2014)
In this paper, we introduce the concept of pointwise statistical convergence of order a of sequences of fuzzy mappings. Furthermore we give the concept of alpha-statistically Cauchy sequence for sequences of fuzzy mappings and prove that it is equivalent to pointwise statistical convergence of order alpha of sequences of fuzzy mappings. Also some relations between S beta(F)-statistical convergence and strong w(P)(alpha)(F)-summability are given.
Keywords: Cesaro summability; pointwise statistical convergence; sequences of fuzzy mappings